2023
DOI: 10.3390/electricity4010006
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Optimal Reactive Power Compensation in Distribution Grids by Using Industrial Compensation Systems

Abstract: This paper presents a method for integrating industrial consumers owning compensation systems as alternative reactive power sources into grid operating processes. In remuneration, they receive a market-based provision of reactive power. The aim is to analyze the potential of reactive power compensation systems of industrial companies connected to medium-voltage (10 kV–30 kV) AC grids in order to increase the reactive power ability of distribution grids. Measurement methods and reactive power potential results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Their work provides the real implementation approaches for the purpose of improving the grid's functionality. [12] In the same vein, Lin's et al paper have made an assessment on a reactive power compensation approach of electric vehicles connected to distribution networks that could result in voltage constraints at extreme operating state. These researchers are finding out about the supportive role that electric vehicles assume on power grids and the related possibility of reactive power increase and preventing it.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Their work provides the real implementation approaches for the purpose of improving the grid's functionality. [12] In the same vein, Lin's et al paper have made an assessment on a reactive power compensation approach of electric vehicles connected to distribution networks that could result in voltage constraints at extreme operating state. These researchers are finding out about the supportive role that electric vehicles assume on power grids and the related possibility of reactive power increase and preventing it.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This characterization comes from the fact that many methods and technologies are present in the process and they all move towards achieving a high-quality grid, which is reliable, efficient, and can withstand any challenge, including changing operational conditions and rapid renewable energy integration. [12] [14] Improving the voltage profile and active power loss in electrical power distribution systems through optimal capacitor placement is done using genetic algorithms. The study employs loss sensitivity analysis and GA, demonstrating a multi-purpose goal function for the simultaneous reduction of losses and improvement of the voltage profile.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Practical application and research of static thyristor compensators (STC), accomplished by various known electrical engineering stake-holders (ABB, General Electric, Schneider Electric, Mitsubishi, Siemens, Westinghouse, Hitachi Energy, etc.) have shown that STC designs based on the thyristor-controlled shunt reactors, on the so-called thyristor-reactor groups, and higher harmonics parallel filters, commonly called a compensating filter [6,7] are most suitable for use in power supply systems. In Jordan, Ukraine and many other countries, a full range of scientific research, design, and engineering development related to this field is being carried out [8,9], which proves the relevance of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Another research project presented the design and implementation of a prototype for an outage and voltage drop recorder. This recorder serves as a low-cost alternative for studying the quality of the voltage wave in distribution networks [33]. This paper will first address some definitions related to power quality and will then describe in general terms the design and construction of the protocol for recording two disturbances of the voltage waveform, interruptions and voltage drops.…”
Section: Introductionmentioning
confidence: 99%